2017
DOI: 10.14356/kona.2017019
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Wetting Behaviour of Poor Wetting Food Powders and the Influence of Temperature and Film Formation

Abstract: Characterisation of the wettability of five poor wetting food powders was performed using static immersion and contact angle measurements. The effect of temperature (20, 50 and 70 °C) on wettability showed varying effects on the powders. Higher temperatures majorly improved the wettability of chocolate and high fat powders but worsened the wettability of sodium caseinate and milk protein isolate. Rate-limiting regime testing was performed by pouring a fixed mass of powder on to the surface of water in an agita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…Fitzpatrick et al . (2017) showed that increasing water temperature improved wettability; for example, skimmed milk powder (132 µm) presented a wettability value of 51 s at 20 °C, 16 s at 50 °C and 10 s at 70 °C. In this, similar research results (at 35 °C) were obtained (7 s for ground puffs A and 9 s for ground puffs B) without significant differences between them ( P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Fitzpatrick et al . (2017) showed that increasing water temperature improved wettability; for example, skimmed milk powder (132 µm) presented a wettability value of 51 s at 20 °C, 16 s at 50 °C and 10 s at 70 °C. In this, similar research results (at 35 °C) were obtained (7 s for ground puffs A and 9 s for ground puffs B) without significant differences between them ( P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The high protein increases the protein-protein interaction between the particles which resist the movement of water into particle (Silva & O'Mahony, 2017). In some studies, it was found that how the composition of food powders majorly influences the wettability, that is, the high amount of fat present in food powders provides poorest wettability to powders due to the hydrophobic nature of fat (Fitzpatrick, Salmon, Ji, & Miao, 2017). Similar study by Crowley et al (2015) found that the contact angle of milk protein concentrate increases with larger particle size and higher protein content of the milk powder.…”
Section: Powder Wettability (Contact Angle)mentioning
confidence: 99%
“…The wettability of WPI powders was measured gravimetrically using a modified immersional wetting approach [28,29]. Powder samples were poured onto ultrapure water and allowed to wet and sink for 1 h. Powder that remained on the water surface was carefully removed with a spoon, weighted and dried overnight at 105 °C.…”
Section: Wettability and Dissolution Characteristics Of Whey Protein Isolate Powdersmentioning
confidence: 99%